Hybrid Composites Based on Thermoplastic Polyurethane With a Mixture of Carbon Nanotubes and Carbon Black Modified With Polypyrrole for Electromagnetic Shielding - Bertolini, Mayara C.; Ramoa, Sílvia D. A. S.; Merlini, Claudia; Barra, Guilherme M. O.; Soares, Bluma G.; Pegoretti, Alessandro (Frontiers in Materials, 2020)
Hybrid conducting composites comprising thermoplastic polyurethane (TPU) and mixtures of carbon black modified with polypyrrole (CB-PPy) and carbon nanotubes (CNT) were prepared by melt mixing process. The electrical conductivity, rheological properties and electromagnetic shielding effectiveness (EMI SE) of TPU/CB-PPy and TPU/CNT composites were also carried out and compared to those results observed for TPU/CB-PPy/CNT hybrid composites. TPU/CNT composites show a very sharp insulator-conductor transition and the electrical percolation threshold was about 1 wt% of CNT, which was lower than that found for TPU/CB-PPy (7 wt%). Moreover, EMI SE values of TPU/CNT composites were higher than those for TPU/CB-PPy due to the denser CNT conductive pathway into TPU matrix. In order to achieve the highest electrical conductivity and EMI SE values, considerable amount of CB-PPy was replaced by CNTs. In fact, the electrical conductivity values increased by combining CB-PPy and CNT, resulting in hybrid composites of TPU/CB-PPy/CNT with higher EMI SE values when compared to TPU/CB-PPy composites. The present study demonstrates the potential use of hybrid polymer composites containing 5 wt% or 8 wt% of CB-PPy/CNT at specific CB-PPy/CNT ratios that reach an EMI SE value as high as -20 dB, indicating the potential use of these materials for electromagnetic shielding application in the X-band frequency region.